Analysis of bilateral breast carcinomas: a profile of patients at a reference service - Pasetto, Camila Vitola; Batista, Bruno Ribeiro; Budel, Lucas Roskamp; Andreoli, Mariana De Nadai; Budel, Vinicius Milani (Mastology, 2021)
Objective: To select cases of bilateral breast carcinoma (BBC) of patients seen at Hospital de Clínicas of Paraná, besides recognizing clinical and family characteristics, histological and immunohistochemical pattern, and incidences of synchronic/metachronic tumor in these patients. Method: Observational and analytical study of BBC cases of patients treated at Hospital de Clínicas of Paraná, from 2003 to 2019, developed from the analysis of medical records. Result: A total of 42 patients with BBC were selected. The incidence of BBC was 3.64%. All patients were women, mostly of white skin color and postmenopausal, with an average age of 51.82 years. Half patients showed a positive family history for cancer, with breast cancer present in 46%, ovarian cancer in 16%, and other topographies in 68%. In this sample, the synchronous tumor was present in 55% of patients, and the metachronous tumor, in 45%. Regarding patients’ initial clinical staging, 61% had a locally advanced tumor at diagnosis. Both in the group of synchronic and metachronic tumors, the ductal subtype was the most frequent. Regarding the immunohistochemical subtype, patients in both groups had Luminal B tumors more frequently. In the group of metachronic tumors, the average time between the diagnosis of the first tumor and the second tumor was 5.68 years. Conclusion: In this sample, BBC is associated with a relevant family history, with a synchronic presentation pattern, from histology to ductal and immunohistochemistry to Luminal B as the most frequent.